The Effect of Service Quality and Food Products on Guest Satisfaction at The Flavor Hotel Citradream Semarang Restaurant - Sapto Supriyanto; Ray Octafian (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The phenomenon that occurs in the field shows that from the results of the suggestion box there are still complaints from guests who use the restaurant's services, these complaints include the lack of garnishes or the appearance of food and drinks that are less attractive, the lack of menu variations on the food and drinks served, the lack of friendliness of some employees. restaurants in providing service, especially when crowded conditions, limited menu books, slow and unresponsive service. These questions aim to determine and analyze the effect of service quality on guest satisfaction at The Flavor Citradream Hotel Semarang Restaurant, to determine and analyze the effect of food product quality on guest satisfaction at The Flavor Citradream Hotel Semarang Restaurant, to determine and analyze the effect of service and the quality of food products together on guest satisfaction at The Flavor Citradream Hotel Semarang Restaurant. This research is a way to find out, discuss, analyze and conclude in depth about the influence of food product quality and service on guest satisfaction at Restaurant The Flavor Hotel Citradream Semarang. The variable quality of food products is the variable that has the most influence on guest satisfaction when visiting Restaurant The Flavor Hotel Citradream Semarang.